(untitled) - Yeager, Chuck (New York, 1985)
YA Bona fide heroes are a rare breed, and while Chuck Yeager would be the first to deny he was one, his life story tells a different tale. Here he describes his early life in the hills of West Virginia; his years as fighter pilot in World War II, where he was shot down in occupied France and escaped with the help of the French Resistance; his love of flying. His coolness under pressure; his knowledge of how everything on his plane worked; and his extraordinary luck saved his life in many instances. Brash, opinionated, stubborn and given to wild antics, Yeager also comes across as a man of integrity and courage. Yeager both lived and made aviation history. He tells his story vividly and pulls no punches in describing the events and the people who made history with him. Diana Hirsch
Keywords: Air pilots,Phi công hàng không; Biography,Tiểu sử; United States,Hoa Kỳ